Procedural Justice in Performance Evaluation: The Role of Instrumental and Non-Instrumental Voice in Performance Appraisal Discussions - Korsgaard, M. Audrey; Roberson, Loriann (Journal of Management, 1995)
This study examined the role of subordinate voice in creating positive attitudes in the performance appraisal context. Two aspects of voice, instrumental and non-instrumental, were assessed. Both aspects of voice were related to satisfaction with the appraisal, while only non-instrumental voice had an impact on attitudes toward the manager. Implications for procedural justice and performance appraisal are discussed.